Role of Serotonin in the Maintenance of Inflammatory State in Crohn’s Disease - Simona Pergolizzi; Alessio Alesci; Antonio Centofanti; Marialuisa Aragona; Socrate Pallio; Ludovico Magaudda; Giuseppina Cutroneo; Eugenia Rita Lauriano (Biomedicines, 2022)
Crohn’s disease (CD) is a chronic intestinal inflammation considered to be a major entity of inflammatory bowel diseases (IBDs), affecting different segments of the whole gastrointestinal tract. Peripheral serotonin (5-HT), a bioactive amine predominantly produced by gut enterochromaffin cells (ECs), is crucial in gastrointestinal functions, including motility, sensitivity, secretion, and the inflammatory response. These actions are mediated by a large family of serotonin receptors and specialized serotonin transporter (SERT) located on a variety of cell types in the gut. Several studies indicate that intestinal 5-HT signaling is altered in patients with inflammatory bowel disease. Paraformaldehyde-fixed intestinal tissues, obtained from fifteen patients with Crohn’s disease were analyzed by immunostaining for serotonin, Langerin/CD207, and alpha-Smooth Muscle Actin (α-SMA). As controls, unaffected (normal) intestinal specimens of seven individuals were investigated. This study aimed to show the expression of serotonin in dendritic cells (DCs) and myofibroblast which have been characterized with Langerin/CD207 and α-SMA, respectively; furthermore, for the first time, we have found the presence of serotonin in goblet cells. Our results show the correlation between different types of intestinal cells in the maintenance of the inflammatory state in CD linked to the recall of myofibroblasts.